(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tourism Business has been a vital component of Indian Culture and Heritage. It is the most vibrant tertiary activity and a multibillion-dollar sector in India. The travel and tourism industry contributes considerably to socioeconomic growth through job creation, foreign exchange gains, and infrastructural development. In recent years, India has experienced rapid expansion in the tourism industry. Currently, India is a popular destination for both international and local visitors. India allows overseas travelers to appreciate and experience the country’s cultural variety. According to official estimates, tourism in India has surpassed the world tourism sector in terms of growth, the volume of international travelers, and even income. The tourist business in India is seeing rapid expansion.